Detecting and identifying arbitrage in the spot foreign exchange market. Issue 1 (2nd January 2020) - Cui, Zhenyu; Qian, Wenhan; Taylor, Stephen; Zhu, Lingjiong
Abstract : We propose a theoretical framework for the detection and identification of triangular arbitrage opportunities between currency exchange rates in the spot foreign exchange market. We obtain sufficient conditions for the exclusion of triangular arbitrage opportunities in the setting of non-trivial transaction costs in terms of the currency rates of the market under consideration. Then we propose an efficient computational approach which can detect triangular arbitrage opportunities in real time. Finally, we consider numerical studies that utilize spot currency exchange rate quotes to substantiate and present applications of the theoretical findings as well as to demonstrate the efficiency of the proposed computational arbitrage detection and identification methods.